Crystallization and X-ray analysis of all of the players in the autoregulation of the ataRT toxin–antitoxin system - Jurėnas, Dukas (Acta Crystallogr F Struct Biol Commun, 2018)
The ataRT operon from enteropathogenic Escherichia coli encodes a toxin–antitoxin (TA) module with a recently discovered novel toxin activity. This new type II TA module targets translation initiation for cell-growth arrest. Virtually nothing is known regarding the molecular mechanisms of neutralization, toxin catalytic action or translation autoregulation. Here, the production, biochemical analysis and crystallization of the intrinsically disordered antitoxin AtaR, the toxin AtaT, the AtaR–AtaT complex and the complex of AtaR–AtaT with a double-stranded DNA fragment of the operator region of the promoter are reported. Because they contain large regions that are intrinsically disordered, TA antitoxins are notoriously difficult to crystallize. AtaR forms a homodimer in solution and crystallizes in space group P6(1)22, with unit-cell parameters a = b = 56.3, c = 160.8 Å. The crystals are likely to contain an AtaR monomer in the asymmetric unit and diffracted to 3.8 Å resolution. The Y144F catalytic mutant of AtaT (AtaT(Y144F)) bound to the cofactor acetyl coenzyme A (AcCoA) and the C-terminal neutralization domain of AtaR (AtaR(44–86)) were also crystallized. The crystals of the AtaT(Y144F)–AcCoA complex diffracted to 2.5 Å resolution and the crystals of AtaR(44–86) diffracted to 2.2 Å resolution. Analysis of these structures should reveal the full scope of the neutralization of the toxin AtaT by AtaR. The crystals belonged to space groups P6(5)22 and P3(1)21, with unit-cell parameters a = b = 58.1, c = 216.7 Å and a = b = 87.6, c = 125.5 Å, respectively. The AtaR–AtaT–DNA complex contains a 22 bp DNA duplex that was optimized to obtain high-resolution data based on the sequence of two inverted repeats detected in the operator region. It crystallizes in space group C222(1), with unit-cell parameters a = 75.6, b = 87.9, c = 190.5 Å. These crystals diffracted to 3.5 Å resolution.